Cross Sectional: Dukungan Sosial dan Resiliensi Perawat - Okti Rahayu Asih; Rahmi Fahmy; Dwi Novrianda; Henny Lucida; Vetty Priscilla; Zifriyanthi Minanda Putri (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Resilience is an essential element to be built in the nursing profession in order to overcome challenges and difficulties in the workplace. Relationship and effective support that comes from family, friends and peers are factors that influence resilience. To examine the relationship between social support and nurse resilience. This research applied a quantitative design with cross sectional approach. The samples were taken by proportional random sampling and 110 nurses were chosen as the samples.  The instruments in this study were CD-RISC 10 and MSPSS with modified.  There is a relationship between social support and nurse resilience. Suggestion: Hospital management may design an innovative and creative programs to increase nurses’ perceived social support such as family gathering programs, family hospital tour programs and mentoring as an effort to increase their resilience